Assessment of Anemia in Patients with Various Types of Inflammatory Bowel Disease under Medical Therapy - Seyed Mohammad Hassan Emami; Ali Gharavinia; Mohammad Emadoddin Habibi; Farzaneh Habibi; Sadegh Baradaran-Mahdavi; Abdalmahdi Baghaei (مجله دانشکده پزشکی اصفهان, 2018)
Background: Anemia is a usual systemic complication of inflammatory bowel disease (IBD) and can be presented in combination of iron deficiency anemia (IDA) and anemia of chronic disease (ACD). In the present study, anemia in IBD was assessed.